Graphene aerogel for electromagnetic shielding and preparation method thereof
Through interface static self -assembly and polyamide carbonization coating technology, the graphene gas gel has the problem of high -electromagnetic shielding performance and super flexibility while maintaining the advantages of light porosity, and realizing efficient electronic transmission and efficient efficiency Load transmission, suitable for 3D printing technology.
Patent Information
- Application Number
- CN202411265434.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to achieve a double breakthrough in high electromagnetic shielding performance and super elasticity while maintaining the lightweight and porous advantages of graphene aerogels. The commonly used manufacturing methods are complex, costly and limited in application fields.
Using an interfacial electrostatic self-assembly strategy, a GO-based water-in-oil emulsion is prepared, and after high-temperature heat treatment, macromolecular polyamic acid is introduced for carbonization coating to form interfacial welding, dense pore walls and enhanced lamellar connections, promoting rapid Electron transport and efficient load transfer.
The preparation of light -quality high -elastable graphene gas gel has excellent electromagnetic shielding performance and thermal insulation performance. At the same time, it does not need to add additional adhesive ingredients. It is suitable for 3D printing technology to achieve the appropriate shape and customized design of the material.
Smart Images

Figure CN119349560A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocomposite materials, and in particular to a graphene aerogel for electromagnetic shielding and a preparation method thereof. Background Art
[0002] Carbon materials are ideal materials for achieving high-efficiency electromagnetic shielding performance due to their light weight, large specific surface area, good thermal stability, high electrical conductivity and excellent mechanical properties. Among them, carbon nanotubes, graphene nanosheets, carbon fibers and carbon black can be mixed with a variety of substrates such as polymers and ceramics to prepare new electromagnetic shielding carbon-based composite materials.
[0003] In recent years, graphene aerogel has attracted much attention due to its ultra-low density, wide bandwidth from megahertz to terahertz, and high compressibility. While graphene has high conductivity, its internal three-dimensional network structure further increases the multiple reflections of the incident electromagnetic waves. Therefore, graphene aerogel has good application prospects as an electromagnetic shielding material.
[0004] Graphene aerogels are prepared based on graphene oxide (GO), in which oxygen-containing groups can prevent the restacking of graphene flakes and form a uniform dispersion. Using colloidal GO suspension as a precursor is a feasible method for economical and efficient large-scale production of graphene aerogels. Self-assembly of GO nanosheets into three-dimensional porous structures is a common method for preparing elastic graphene aerogels, and its driving force is usually based on hydrogen bonds, van der Waals forces, etc. Therefore, GO three-dimensional networks are constructed by various methods such as hydrothermal reduction, chemical reduction and cross-linking techniques. For the preparation of graphene aerogels, template method, self-assembly method and 3D printing can usually be used. Reasonable microstructure design can give graphene aerogels high compressibility and high elasticity, such as honeycomb structure, layered structure and negative Poisson's ratio structure. Therefore, researchers have been committed to constructing three-dimensional porous structures with continuous conductivity to achieve the requirements of light weight and efficient electromagnetic shielding.
[0005] Furthermore, it is known that the introduction of nanomaterials and polymers can be used to enhance the interaction between graphene nanosheets, thereby achieving the elasticity of the three-dimensional structure of graphene aerogels. So far, researchers have prepared a variety of GO-based composite aerogels that can achieve excellent mechanical resilience under 50% to 80% compression strain, while their electromagnetic shielding performance is comparable to or even better than that of traditional metal materials. In addition, they also focus on other properties of these materials, such as the characteristics of GO materials.
[0006] At present, in order to prepare lightweight superelastic graphene-based electromagnetic shielding materials, the commonly used measures include: introducing heterogeneous components and reasonable structural design, for example: using the introduction of polymers, carbon nanotubes and ceramics or regulating the internal microscopic pore structure to enhance the interaction between sheets and promote the transfer of effective loads to improve its mechanical properties. Chinese invention patent application CN114891267A discloses a highly elastic hydrophobic graphene / nanocellulose composite aerogel, in which the hydrogen bonds between one-dimensional nanocellulose and graphene oxide are used to provide structural support and improve mechanical strength, prevent graphene sheets from aggregating during chemical reduction, and reduce the degradation and deformation of graphene aerogel during drying. However, the maximum compressive strain of the aerogel can only reach 50%, and the plastic deformation produced is relatively large. Chinese invention patent CN112536004B discloses a high temperature resistant elastic graphene aerogel material and its preparation method, which constructs a honeycomb-shaped orderly macroporous structure. The pore wall of the aerogel is covered with a silicon dioxide nano-thin layer. The aerogel can still achieve a rebound rate of 100% under 30% compression, showing excellent rebound performance. However, the density of the aerogel is relatively high (20-60 mg cm -3 ). Chinese invention patent application CN108165018A discloses a silicone rubber / graphene / silver nanowire nanocomposite material for electromagnetic shielding and its preparation method. This material has high conductivity and good electromagnetic shielding performance, but consumes a lot of energy in the manufacturing process, the drying process takes a long time, and the prepared aerogel has small pores, thin pore walls, and poor elasticity. The above manufacturing method is complicated, the cost is high, and the application field is limited, so the material cannot be used on a large scale.
[0007] Specifically, although the above-mentioned prior art has made some explorations in the preparation of lightweight, high compression resilience and high electromagnetic shielding performance graphene aerogels, it has been found in long-term production practice that these methods have the following problems: (1) The lightweight and porous structure will lead to fragile connections between the pore walls, making it difficult to obtain a continuous high-density conductive network and achieve efficient load transfer, thereby damaging the conductivity and mechanical resilience of the aerogel, making it difficult to adapt to many complex deformations in extreme applications, limiting its further development; (2) The introduced heterogeneous components reduce the conductivity of the aerogel; (3) Due to the addition of additives, it is difficult to prepare low-density 3D materials. It can be seen that it is difficult to achieve high electromagnetic interference shielding performance and superelasticity of lightweight graphene aerogels at the same time.
[0008] In summary, although current research has achieved certain results in improving the comprehensive performance of graphene aerogels, how to overcome the contradiction between mechanical elasticity and conductivity while maintaining its lightweight and porous advantages and achieve a dual breakthrough in high electromagnetic shielding performance and superelasticity is still a key scientific problem that needs to be solved urgently in the future.
[0009] In view of this, the present invention is proposed. Summary of the invention
[0010] The purpose of the present invention is to provide a novel and simple method, which adopts an interfacial electrostatic self-assembly strategy to first prepare a GO-based oil-in-water emulsion, and then form a special structure through the negatively charged groups on the surface of GO and the positively charged ligands. Further, after high-temperature heat treatment, the introduced macromolecular polyamic acid is further carbonized and coated on the highly reduced graphene sheets to form interface welding, and the dense pore walls and enhanced sheet connection further promote rapid electron transmission and efficient load transfer, thereby forming a lightweight and highly elastic graphene aerogel with excellent electromagnetic shielding performance.
[0011] Furthermore, the present invention also provides a graphene aerogel obtained based on 3D printing, wherein the graphene aerogel product has a microporous structure adjustable at the micron level and can have an extremely low apparent density, while also having good mechanical resilience and electromagnetic shielding properties.
[0012] To achieve the above objectives, the present invention adopts the following technical solutions.
[0013] The present invention provides a method for preparing a graphene aerogel for electromagnetic shielding, comprising the following steps:
[0014] 1) dispersing graphene oxide and polyamic acid in water to obtain a graphene oxide / polyamic acid dispersion;
[0015] 2) mixing the oil solution and the graphene oxide / polyamic acid dispersion to obtain a water-in-oil emulsion;
[0016] 3) The water-in-oil emulsion is placed into a mold or 3D printed, and then sequentially frozen, freeze-dried, and thermally annealed, and the residual ligand compound containing an amino group is removed by heating under an inert gas atmosphere. A light and highly elastic graphene aerogel is obtained; the light and highly elastic graphene has an isotropic closed-cell structure, and the polyamic acid can be coated on the outside of the graphene sheet and at the connection between the sheets after high-temperature carbonization treatment to form an integrated structure, which plays a role in enhancing the interface.
[0017] Preferably, in step 1), the mass ratio of graphene oxide to polyamic acid contained in the graphene oxide / polyamic acid dispersion is (4-0.5):1; wherein the solid content of graphene oxide in the graphene oxide / polyamic acid dispersion is 2-8 mg mL -1 ;
[0018] The concentration of graphene oxide contained in the graphene oxide / polyamic acid dispersion is 5 to 40 mg mL -1
[0019] Preferably, in step 2), the volume ratio of the oil solution to the graphene oxide / polyamic acid dispersion is 1:(1-4).
[0020] Preferably, in step 2), the oil phase is an oil solution containing an amine-containing ligand compound; wherein the concentration of the amine-containing ligand compound is 2.5 to 20 mg mL -1 .
[0021] Preferably, the ligand compound containing an amine group is selected from one or more hydrocarbyl amines;
[0022] Preferably, the hydrocarbon group in the hydrocarbon amine is selected from hydrocarbon groups with 3 to 50 carbon atoms, preferably but not limited to cyclohexane, toluene, ether, ethylene dichloride, acetone, cyclohexanone and the like.
[0023] Preferably, in step 1), the dispersion process is stirred for 1-2 hours.
[0024] Preferably, in step 2), the emulsification conditions are emulsification at a speed of 1000 to 3000 rpm for 0.5 to 5 min;
[0025] Preferably, the stirring speed is 1300-1600 rpm, and the stirring time is 1.5-3.5 min.
[0026] Preferably, in step (3), the freeze drying is: first freezing at 80 to -10°C for 12 to 24 hours, then placing in a freeze dryer, the temperature of the cold trap of the freeze dryer is -80°C to -50°C, the freeze drying pressure is 1 to 30 Pa, and freeze drying is performed for 24 to 96 hours;
[0027] The temperature of the thermal annealing treatment is 300-1600°C, and the time of the thermal annealing treatment is 1-3h;
[0028] The heating rate to the temperature of the thermal annealing treatment is 1-10℃min -1 ;
[0029] The reaction is carried out in an inert atmosphere, wherein the inert atmosphere is an argon atmosphere, wherein the argon gas intake rate is 2 to 40 mL min -1 ;
[0030] Preferably, the temperature of the thermal annealing treatment is 800-1600° C., and the time of the thermal annealing treatment is 1.5-2.5 hours.
[0031] Preferably, the heating rate to the temperature of the thermal annealing treatment is 4-6°C min -1 ;
[0032] Preferably, the argon inlet rate is 15-25 mL min -1 .
[0033] The invention provides a graphene aerogel for electromagnetic shielding, and the graphene aerogel for electromagnetic shielding is obtained by the preparation method.
[0034] Preferably, the graphene aerogel has a pore size distribution of 30 to 100 μm, a porosity of at least 95%, and an apparent density of 3 to 15 mg cm -3 , conductivity is 300~1000S m -1 ;Electromagnetic shielding rate is 20~90dB; thermal conductivity is 20~50mWm -1 K -1 ;
[0035] Preferably, the graphene aerogel has a resilience of ≥90% under a compression strain of 90%; a plastic deformation of ≤15% after 1000 cycles of 50% compression strain; and a maximum stress reduction of ≤25% after 1000 cycles of 50% compression strain.
[0036] The graphene oxide and polyamic acid of the present invention are dispersed in water to form a specific water phase, and a water-in-oil emulsion is formed by combining a specific water phase and an oil phase. After high-temperature heat treatment, the introduced macromolecular polyamic acid is further carbonized and coated on the highly reduced graphene sheet to form an interface welding, forming a dense pore wall and an isotropic closed-cell structure, and obtaining a lightweight and highly elastic graphene aerogel with excellent electromagnetic shielding performance and thermal insulation performance. Furthermore, the water-in-oil emulsion provided by the present invention meets the ink requirements of 3D printing, prepares a lightweight GO macro material with a multi-level structure and a charge transfer network that is accurately controllable, and optimizes its electromagnetic shielding performance.
[0037] Beneficial effects of the present invention:
[0038] 1) The present invention utilizes the combination of a specific water phase and an oil phase to form an oil-in-water emulsion. The electrostatic interaction between the ligand in the oil phase and the graphene oxide nanosheets in the water phase enables the nanoparticle surfactant to be assembled in an orderly manner at the oil-water interface, forming a dense pore wall and an isotropic closed-pore structure.
[0039] 2) The macromolecular polyamic acid introduced in the present invention is further carbonized and coated on the highly reduced graphene sheets to form interface welding. The dense pore walls and enhanced sheet connection further promote rapid electron transmission and efficient load transfer, thereby forming a graphene aerogel with excellent mechanical resilience and electromagnetic shielding properties;
[0040] 3) The present invention does not require the addition of additional thickening components and can still provide suitable viscosity at a lower solid content, meeting the requirements of 3D printing inks and achieving conformability and customized design of electromagnetic shielding materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] FIG. 1( a ) shows the change in fluidity of the graphene oxide / polyamic acid dispersion obtained in Example 1 of the present invention before and after emulsification;
[0043] FIG1( b ) is a display of the fluidity of emulsions prepared from graphene oxide solutions of different concentrations obtained in corresponding Examples 1 to 5 of the present invention;
[0044] FIG1( c ) shows the rheological properties (viscosity) of the emulsion obtained in the corresponding embodiment 6 of the present invention;
[0045] FIG. 1( d ) shows the rheological properties (modulus) of the emulsion obtained in the corresponding embodiment 6 of the present invention.
[0046] FIG2( a) is a physical picture of the graphene aerogel in the corresponding embodiments 1 to 4 of the present invention;
[0047] FIG2( b ) is a diagram showing the lightweight graphene aerogel in the corresponding embodiment 1 of the present invention;
[0048] FIG2( c ) is a physical picture of the 3D printed GO scaffold in the corresponding embodiment 6 of the present invention.
[0049] FIG3( a) is a SEM image of the pore structure of the graphene aerogel in Example 4 of the present invention;
[0050] FIG3( b ) is a SEM image of the pore structure of the graphene aerogel in the corresponding embodiment 1 of the present invention;
[0051] FIG3( c ) is a “Y”-shaped connection obtained by enlarging the internal pore structure of the graphene aerogel in the corresponding embodiment 4 of the present invention.
[0052] FIG4( a) is a SEM image of the surface of the 3D printed GO scaffold in the corresponding embodiment 6 of the present invention;
[0053] FIG4( b ) is an enlarged SEM image of the surface of the 3D printed GO scaffold in the corresponding embodiment 6 of the present invention;
[0054] FIG4( c ) is a SEM image of a cross section of a 3D printed GO scaffold in the corresponding embodiment 6 of the present invention;
[0055] Figure 4(d) is an enlarged SEM image of the cross section of the 3D printed GO scaffold in the corresponding embodiment 6 of the present invention.
[0056] FIG5( a ) is a stress-strain curve of the mechanical resilience of the graphene aerogel under 90% compression strain in Example 1 of the present invention;
[0057] FIG5( b ) is the stress-strain of the mechanical resilience of the graphene aerogel in the corresponding embodiment 1 of the present invention under 50% strain after 1000 cycles of compression-release;
[0058] FIG. 5( c ) shows the apparent density of the graphene aerogels in the corresponding embodiments 1 to 5 of the present invention and the plastic deformation after 1000 cycles of 50% compression strain.
[0059] FIG6( a ) is a diagram showing the conductivity of graphene aerogels in corresponding embodiments 1 to 5 of the present invention;
[0060] FIG6( b ) is a diagram showing the conductivity of graphene aerogels in corresponding embodiments 1 to 5 of the present invention; and the electromagnetic shielding performance of graphene aerogels in corresponding embodiments of the present invention;
[0061] FIG6( c ) shows the conductive and thermal insulation properties of the graphene aerogels in the corresponding embodiments 1 to 4 of the present invention.
[0062] FIG. 7( a ) shows the mechanical resilience of the 3D printed GO scaffold in the corresponding embodiment 6 of the present invention;
[0063] FIG7( b ) shows the electromagnetic shielding performance of the 3D printed GO support in the corresponding embodiment 6 of the present invention. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0065] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0066] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0067] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0068] In this specification, the term "room temperature" or "normal temperature" refers to an ambient temperature of 23±2°C.
[0069] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" or "mass %" used means weight or mass percentage.
[0070] In the present specification, the use of “substantially” / “essentially” means that the deviation is not more than 3%, preferably not more than 1%, based on a reference or ideal situation.
[0071] In this specification, unless otherwise stated, "plurality" means that there are two or more.
[0072] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0073] The present invention primarily provides a method for preparing an emulsion based on GO material for electromagnetic shielding and an aerogel product based on the emulsion, wherein an aqueous dispersion of a specific composition is mixed with an oil solution, emulsified to obtain an oil-in-water emulsion, and then directly placed into a mold or 3D printed to obtain an aerogel product.
[0074] Furthermore, the present invention is mainly based on the following insights:
[0075] After the water dispersion containing GO is mixed with the positively charged oil solution containing amino long-chain ligands to form an oil-in-water emulsion system, due to the presence of negatively charged groups on the GO surface, the GO nanosheets in the water phase and the positively charged ligands in the oil phase are driven by electrostatic forces during the emulsification process to form a GO-based nanosheet surfactant in situ at the water / oil interface, which greatly reduces the interfacial tension. The protective layer formed by its blocking can effectively prevent the aggregation and Ostwald ripening of the emulsion droplets, which is conducive to the construction of an isotropic closed-cell structure.
[0076] Furthermore, by introducing macromolecular polyamic acid, it can be carbonized and coated on highly reduced graphene sheets after high-temperature heat treatment to form interface welding. The dense pore walls and enhanced sheet connection further promote rapid electron transmission. At the same time, the nano-folds introduced by polyamic acid can act as nano-scale springs to provide large out-of-plane deformation. Further heat treatment to remove ligands can obtain graphene aerogels with high elasticity, high conductivity, high porosity, and ultra-lightness, which can be used in the fields of electromagnetic shielding and heat insulation.
[0077] In addition, the prepared oil-in-water emulsion has ideal viscosity and modulus to meet the needs of 3D printing. Combined with ink direct writing technology, lightweight GO components with multi-level structures and accurately controllable charge transfer networks can be prepared, providing useful inspiration for the development of lightweight electromagnetic shielding components with customizability and shape adaptability.
[0078] <First aspect>
[0079] In the first aspect of the present invention, a water-in-oil emulsion and a preparation method thereof are provided. The emulsion comprises an oil phase as a continuous phase and an aqueous phase as a dispersed phase. In addition, the ratio of the aqueous phase system V1 to the oil phase system V2 in the water-in-oil emulsion is (4-1):1, preferably, V1:V2 is 2:1.
[0080] Aqueous phase: The aqueous phase of the present invention may be an aqueous dispersion, wherein the aqueous dispersion includes GO material as a conductive material, water-soluble polyamic acid and water as a dispersant.
[0081] The graphene oxide contained in the graphene oxide / polyamic acid dispersion of the present invention has 1 to 6 layers (e.g., 1, 2, 3, 4, 5 or 6 layers); preferably, the graphene oxide contained in the graphene oxide / polyamic acid dispersion has 1 layer, i.e., a single layer of graphene oxide; the concentration of the graphene oxide contained in the graphene oxide / polyamic acid dispersion is 5 to 40 mg mL -1 (e.g. 2, 5, 10, 15, 20, 25, 30, 35, or 40 mg mL -1 ) is preferably 8 mg mL -1 .
[0082] According to some preferred embodiments, the mass ratio of graphene oxide and polyamic acid contained in the graphene oxide / polyamic acid dispersion is (4-0.5): 1 (e.g., 4: 1, 3: 1, 2: 1, 1: 1, 0.5: 1), more preferably 1: 1. If the amount of polyamic acid relative to graphene oxide is too small, it will not have a good lap joint effect, and if the amount of polyamic acid relative to graphene oxide is too large, it will affect the mechanical properties of the material such as elasticity.
[0083] Furthermore, in the aqueous dispersion for forming the aqueous phase of the present invention, in addition to the above-mentioned GO material, other conductive / electromagnetic shielding materials may also be used without affecting the effects of the present invention.
[0084] Oil phase: The oil phase of the present invention may be an oil solution containing an amine-containing ligand compound.
[0085] For the solvent in the oil solution, in a specific embodiment of the present invention, it is an organic solvent. Commonly used organic solvents include one or more of the following: water-insoluble hydrocarbon solvents, ester solvents, ether solvents and ketone solvents. Typical solvents include alkanes, chloroalkanes and aromatic solvents (benzene, toluene), ether, ethylene dichloride, acetone, cyclohexanone, etc.
[0086] In certain cases, the amine-containing ligand compound includes a hydrocarbyl amine having an amine group with one or more terminal amino groups. In addition, in order to improve the stability of the water-in-oil emulsion, in some preferred embodiments, the hydrocarbyl amine according to the present invention may include a long-chain hydrocarbyl amine. Such a hydrocarbyl amine may be an amine containing a hydrocarbyl group with a carbon number between 3 and 50, preferably between 12 and 26, and more preferably between 14 and 24.
[0087] The hydrocarbyl group of the hydrocarbyl amine may have a linear or branched structure, but from the perspective of emulsion stability, a hydrocarbyl amine having a linear structure is more desirable. In addition, the hydrocarbyl group in the hydrocarbyl amine of the present invention may be a saturated or unsaturated alkyl group (eg, containing one or more unsaturated bonds).
[0088] Furthermore, in some specific embodiments of the present invention, the hydrocarbon amine may be octadecylamine or hexadecylamine.
[0089] Preparation of emulsion: The emulsion of the present invention is a water-in-oil emulsion system. Therefore, in some specific embodiments, the water phase as the dispersed phase can be added to the oil phase as the continuous phase to form an emulsion system under emulsification conditions.
[0090] In some specific embodiments, the dispersed phase can be gradually added to the oil phase at room temperature and stirred during the addition process. The stirring method can be rotary mechanical stirring. In some specific embodiments of the present invention, the stirring cycle number can be in the range of 1000 to 3000 rpm to optimize the emulsification effect. The emulsification time can be 0.5 to 5 minutes, preferably 2 minutes.
[0091] The present invention finds that when the water phase and the oil phase are mixed, the GO material in the water phase and the ligand compound containing an amino group in the oil phase will self-assemble, and the GO presents negative charge in the water phase dispersion, and assembles at the oil-water two-phase interface through electrostatic interaction with the positively charged ligand ODA in the oil phase. This nanosheet surfactant gathers at the oil-water interface, greatly reducing the interfacial tension, and the protective layer formed by its blocking can effectively prevent the aggregation and Ostwald ripening of the emulsion droplets, thereby establishing a stable and firm emulsion system. Therefore, the viscosity of such an emulsion does not depend on the solid content of the water phase or the overall emulsion, but basically depends only on the content of the water phase in the emulsion.
[0092] In a further preferred embodiment, the ligand compound containing an amine group may be a hydrocarbon amine, and in particular, the hydrocarbon amine is preferably selected from hydrocarbon groups having 10 to 30 carbon atoms. The reason for selecting such hydrocarbon amine as a ligand is that it has a high migration rate and positive charge after protonation, and its insolubility in water makes it advantageous in interface assembly. In addition, the rheological properties of the emulsion ink are mainly determined by the volume fraction of the emulsion droplets. The interaction between the droplets and the droplets is determined by the basic unit that responds to the applied stress. When the concentration of GO is lower than 5 mg mL -1 When the concentration of GO is increased, the number of nanosheet surfactants is insufficient to block each other to stabilize the oil-water interface, and the emulsion cannot be prevented from agglomerating or self-supporting, and the final result is an unstable mixture rather than a gelled ink. When the concentration of GO is further increased, more nanosheet surfactants will be formed, the stable interface will increase, and the alkyl chains of the ligands anchored on the droplet surface can be effectively entangled, causing the emulsion system to gel, forming a stable emulsion system composed of densely arranged emulsion microspheres.
[0093] This type of GO-based nanosheet surfactant can be used to form a Pickering emulsion ink. By adjusting the GO concentration, the distance between the emulsion microspheres can be reduced. The interaction between the molecular ligands adsorbed on the surface of the microspheres gives the emulsion ink adjustable rheological properties. Furthermore, 3D printing can be used to manufacture GO components with precise microstructures and excellent dimensional stability. This is one of the keys to the preparation of ultra-light, ultra-elastic, and multi-level structure controllable GO-based aerogels in the present invention.
[0094] <Second Aspect>
[0095] The second aspect of the present invention relates to an aerogel product, which may be a microporous product obtained by post-treating the water-in-oil emulsion of the first aspect. In some typical embodiments, the method for preparing the aerogel of the present invention includes a molding step and a post-treatment step.
[0096] The main body of the aerogel is formed in the molding step, and in the post-treatment step, the aerogel is hardened by freeze drying, and then the residual components are removed according to the cleaning step. Further, for the cleaning step, in some specific embodiments of the present invention, the residual ligand compound can be removed by heat treatment, and preferably, the heating temperature of the heat treatment can be above 600°C, more preferably above 1000°C. And, preferably, the heat treatment is carried out in the presence of an inert gas to prevent oxidation of the GO material.
[0097] The skeleton of the aerogel is (substantially only) composed of carbon material, and the aerogel has a microporous structure with an average pore size of 0.1 to 1000 μm and a minimum apparent density of no more than 15 mg cm -3 .
[0098] Preferably, the average pore size of the aerogel may be 30 to 100 μm, more preferably, the average pore size may be 50 to 90 μm, and examples of average pore sizes include 55, 60, 65, 70, 75, 80, 85 μm, etc.
[0099] The apparent density (ratio of mass to drainage volume after wax sealing) can preferably be 3 to 15 mg cm -3 More preferably, it can be 5 to 10 mg cm -3 In addition, the apparent densities that can be listed include 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 mg cm -3 wait.
[0100] Furthermore, the aerogel products of the present invention can show unique morphological characteristics at multiple scales. First, at the pore level, due to the microscopic isotropic closed-cell structure brought about by the characteristics of the emulsion, a large number of hemispherical pores form a robust "Y"-shaped connection. Second, at the pore wall level, the introduction of polyamic acid significantly increases the roughness of the pore wall, causing the pore wall to bend from a flat shape to an arc. Third, at the molecular structure level, after high-temperature thermal annealing treatment, the oxygen-containing groups of the graphene oxide sheets are removed and the polyamic acid undergoes carbonization. This emulsion template method assisted by an interface enhancement strategy gives the aerogel extremely high mechanical resilience, electromagnetic shielding and thermal insulation properties.
[0101] The graphene aerogel prepared based on this water-in-oil emulsion has the characteristics of high porosity, ultra-lightness, superelasticity, high conductivity, high thermal insulation and excellent shielding performance. The conductive pathway formed by the controllable and efficient accumulation of nanosheets gives it excellent conductivity (300-1000 S m) at low density. -1 The rich pore structure and high porosity can effectively reduce the thermal conductivity of solids and gases, making their thermal conductivity 20-50mW m -1 K -1 , for example as low as 25.7mW m -1 K -1 , close to air. In addition, the aerogel prepared by the present invention also has excellent mechanical resilience, with a rebound rate of ≥90% under a compression strain of 90%, a plastic deformation of ≤15% after 1000 cycles of 50% strain, and a maximum stress reduction of ≤25% after 1000 cycles of 50% strain.
[0102] <Third Aspect>
[0103] The third aspect of the present invention relates to a method for 3D printing using the water-in-oil emulsion prepared in the first aspect to obtain an aerogel product. Preferably, from the perspective of printing stability, the ink may be subjected to degassing and other treatments in advance. The post-processing steps are the same as those in the second aspect.
[0104] Furthermore, there are no special requirements for the specific methods and equipment of the 3D printed aerogel products of the present invention, and common foam material 3D printing equipment can be used for preparation. The printing process can be automatically performed by a preset program, or can be completed manually or semi-manually.
[0105] Furthermore, the 3D printed aerogel product of the present invention may have a tertiary structural feature, wherein the primary structure is a microscopic pore structure derived from the properties of the emulsion. In some specific embodiments, for the primary structure, a microporous structure with an average pore size of 30 to 100 μm can be obtained by 3D printing. The secondary structure of the aerogel product is mainly related to the 3D printing equipment, such as the line width of the printed line, which can form a millimeter-level print. The tertiary structure of the aerogel can be the overall macroscopic shape of the aerogel product. The aerogel product of the present invention, wherein the primary, secondary and tertiary structures can all be adjusted, provides more performance combinations for 3D printed products.
[0106] Furthermore, without changing the ink composition, the electromagnetic shielding performance of the aerogel can be effectively improved by adjusting the line width of the printed lines and the stacking method of the printed lines. It can be seen that by combining the ink direct writing technology, a 3D GO macro aerogel material with adjustable multi-level structure can be prepared and its electromagnetic shielding performance can be optimized.
[0107] Example
[0108] The present invention will be further described below through specific embodiments:
[0109] Example 1
[0110] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -1 10 ml of GO dispersion and 10 ml of PAA solution were mixed and stirred at room temperature for 2 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml cyclohexane to prepare 10 mg mL -1solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of cyclohexane and stir at 1500 rpm for 2 min to obtain an oil-in-water emulsion.
[0111] The next step is to prepare graphene aerogel. The above-mentioned water-in-oil emulsion is placed in a mold and placed in a refrigerator at -18°C for 12 hours, and then freeze-dried in a freeze dryer for 48 hours to form a GO / PAA composite aerogel.
[0112] Finally, ODA was removed by high-temperature heat treatment to form highly conductive graphene aerogel. The freeze-dried GO / PAA hybrid aerogel was heat treated at 1000 °C for 2 h in an Ar atmosphere with a gas flow rate of 30 mL min -1 , and naturally cooled to room temperature to obtain lightweight and highly conductive graphene aerogel.
[0113] Example 2
[0114] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -1 13.3 ml of GO dispersion and 6.7 ml of polyamic acid solution were mixed and stirred at room temperature for 2 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml cyclohexane to prepare 10 mg mL -1 solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of cyclohexane and stir at 1300 rpm for 2.5 min to obtain an oil-in-water emulsion.
[0115] Then, the graphene aerogel was prepared by placing the above-mentioned water-in-oil emulsion into a mold and freezing it in a refrigerator at -18°C for 20 hours, and then freeze-drying it in a freeze dryer for 56 hours to form a GO / PAA composite aerogel.
[0116] Finally, ODA was removed by high-temperature heat treatment to form highly conductive graphene aerogel. The freeze-dried GO / PAA hybrid aerogel was heat-treated at 800 °C for 3 h in an Ar atmosphere with a gas flow rate of 25 mL min -1 , and naturally cooled to room temperature to obtain lightweight and highly conductive graphene aerogel.
[0117] Example 3
[0118] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -115 ml of GO dispersion and 5 ml of polyamic acid solution were mixed and stirred at room temperature for 2 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml toluene to prepare 10 mg mL -1 solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of toluene and stir at 1400 rpm for 3 min to obtain an oil-in-water emulsion.
[0119] The next step is to prepare graphene aerogel. The above-mentioned water-in-oil emulsion is placed in a mold and placed in a refrigerator at -18°C for 12 hours, and then freeze-dried in a freeze dryer for 48 hours to form a GO / PAA composite aerogel.
[0120] Finally, ODA was removed by high-temperature heat treatment to form highly conductive graphene aerogel. The freeze-dried GO / PAA hybrid aerogel was heat treated at 1200 °C for 1.5 h in an Ar atmosphere with a gas flow rate of 35 mL min -1 , and naturally cooled to room temperature to obtain lightweight and highly conductive graphene aerogel.
[0121] Example 4
[0122] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -1 16 ml of GO dispersion and 4 ml of polyamic acid solution were mixed and stirred at room temperature for 2 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml cyclohexane to prepare 10 mg mL -1 solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of cyclohexane and stir at 1600 rpm for 2 min to obtain an oil-in-water emulsion.
[0123] Then, the graphene aerogel was prepared by placing the above-mentioned water-in-oil emulsion into a mold and freezing it in a refrigerator at -18°C for 25 hours, and then freeze-drying it in a freeze dryer for 55 hours to form a GO / PAA composite aerogel.
[0124] Finally, ODA was removed by high-temperature heat treatment to form highly conductive graphene aerogel. The freeze-dried GO / PAA hybrid aerogel was heat treated at 1000 °C for 2 h in an Ar atmosphere with a gas flow rate of 30 mL min -1 , and naturally cooled to room temperature to obtain lightweight and highly conductive graphene aerogel.
[0125] Example 5
[0126] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -1 6.7 ml of GO dispersion and 13.3 ml of polyamic acid solution were mixed and stirred at room temperature for 1.5 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml cyclohexane to prepare 10 mg mL -1 solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of cyclohexane and stir at 1500 rpm for 2 min to obtain an oil-in-water emulsion.
[0127] The next step is to prepare graphene aerogel. The above-mentioned water-in-oil emulsion is placed in a mold and placed in a refrigerator at -18°C for 12 hours, and then freeze-dried in a freeze dryer for 48 hours to form a GO / PAA composite aerogel.
[0128] Finally, ODA was removed by high-temperature heat treatment to form highly conductive graphene aerogel. The freeze-dried GO / PAA hybrid aerogel was heat treated at 1000 °C for 2 h in an Ar atmosphere with a gas flow rate of 30 mL min -1 , and naturally cooled to room temperature to obtain lightweight and highly conductive graphene aerogel.
[0129] Example 6
[0130] First, prepare GO Pickering emulsion by preparing 10 mg mL -1 GO dispersion and 10 mg mL -1 10 ml of GO dispersion and 10 ml of PAA solution were mixed and stirred at room temperature for 2 h to prepare 10 mg mL -1 GO / polyamic acid dispersion; 0.35 g ODA (octadecylamine) was dissolved in 35 ml toluene to prepare 10 mg mL -1 solution; add 10 mL of GO / polyamic acid dispersion into 5 mL of toluene and stir at 1500 rpm for 2 min to obtain an oil-in-water emulsion.
[0131] The next step is to prepare graphene aerogel products based on 3D printing. The GO Pickering emulsion is centrifuged and degassed for later use. The printing program is designed with a filament spacing of 1.2 mm, an external size of 20*20 mm, 15 printing layers, and printing parameters adjusted. The needle movement speed is 20 mm / s, the pressure is 9.8 kPa, and a 410 μm needle is used. The printed product is then placed in a -18°C refrigerator and frozen for 12 hours, and then freeze-dried in a freeze dryer for 48 hours to form a GO / PAA composite aerogel. Finally, ODA is removed by high-temperature heat treatment to form a highly conductive graphene aerogel. The freeze-dried GO / PAA mixed aerogel is heat treated at 1000°C in an Ar atmosphere for 2 hours with a gas flow rate of 30 mL min -1 , and naturally cooled to room temperature to obtain a lightweight and highly conductive graphene aerogel based on 3D printing.
[0132] Implementation Results
[0133] For Example 1, the density is 4.2 mg cm -3 , conductivity 572S m -1 , electromagnetic shielding performance 75dB, mechanical resilience under 90% compression strain 98.3%, thermal conductivity in thermal insulation performance 25.7mW m -1 K -1 (See attached Figure 5(c), Figure 6(a)-(c))
[0134] For Example 2, the density is 5.1 mg cm -3 , conductivity 487S m -1 , electromagnetic shielding performance 56dB, mechanical resilience under 90% compression strain 97.6%, thermal conductivity in thermal insulation performance 29.7mW m -1 K -1 (See attached Figure 5(c), Figure 6(a)-(c))
[0135] For Example 3, the density is 7.8 mg cm -3 , conductivity 412S m -1 , electromagnetic shielding performance 44dB, mechanical resilience under 90% compression strain 94.1%, thermal conductivity in thermal insulation performance 30.5mW m -1 K -1 (See attached Figure 5(c), Figure 6(a)-(c))
[0136] For Example 4, the density is 9.6 mg cm -3 , conductivity 349S m -1 , electromagnetic shielding performance 39dB, mechanical resilience under 90% compression strain 91.5%, thermal conductivity in thermal insulation performance 31.5mW m-1 K -1 (See attached Figure 5(c), Figure 6(a)-(c))
[0137] For Example 5, the density is 14.3 mg cm -3 , conductivity 337S m -1 , electromagnetic shielding performance 27dB, mechanical resilience under 90% compression strain 92.2%. (See attached Figure 5(c), Figure 6(a)-(c))
[0138] For Example 6, the density is 3.9 mg cm -3 , electromagnetic shielding performance 61dB, mechanical resilience under 90% compression strain 91.8%. (See Figure 7 (a)-(b))
[0139] The relevant process parameters in the above-mentioned electromagnetic shielding test method are as follows: the electromagnetic shielding effectiveness in the X-band is tested using a waveguide method, which is a conventional technical means in this field.
[0140] The lightweight superelastic graphene aerogel provided by the present invention can be prepared industrially and used for electromagnetic shielding components or aerospace thermal insulation materials.
[0141] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a graphene aerogel for electromagnetic shielding, comprising the following steps: 1) dispersing graphene oxide and polyamic acid in water to obtain a graphene oxide / polyamic acid dispersion; 2) mixing the oil solution and the graphene oxide / polyamic acid dispersion to obtain a water-in-oil emulsion; 3) Freezing, freeze-drying and thermally annealing the water-in-oil emulsion to obtain graphene aerogel.
2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of graphene oxide to polyamic acid contained in the graphene oxide / polyamic acid dispersion is (4-0.5):1; wherein the solid content of graphene oxide in the graphene oxide / polyamic acid dispersion is 2-8 mg mL -1 ; The concentration of graphene oxide contained in the graphene oxide / polyamic acid dispersion is 5 to 40 mg mL -1 .
3. The preparation method according to claim 1, characterized in that: In step 2), the volume ratio of the oil solution to the graphene oxide / polyamic acid dispersion is 1:(1-4).
4. The method for preparing graphene aerogel according to claim 1, characterized in that: In step 2), the oil phase is an oil solution containing an amine-containing ligand compound; wherein the concentration of the amine-containing ligand compound is 2.5 to 20 mg mL -1 .
5. The preparation method according to claim 4, characterized in that: The ligand compound containing an amine group is selected from one or more hydrocarbon amines; Preferably, the hydrocarbyl group in the hydrocarbyl amine is selected from hydrocarbyl groups having 3 to 50 carbon atoms.
6. The preparation method according to claim 1, characterized in that: In step 1), stirring is performed for 1-2 hours during the dispersion process.
7. The method for preparing graphene aerogel according to claim 1, characterized in that: In step 2), the emulsification condition is emulsification at a speed of 1000 to 3000 rpm for 0.5 to 5 minutes; Preferably, the stirring speed is 1300-1600 rpm, and the stirring time is 1.5-3.5 min.
8. The preparation method according to claim 1, characterized in that: In step (3): The freeze drying is as follows: firstly freezing at -80 to -10°C for 12 to 24 hours, then placing in a freeze dryer, the temperature of the cold trap of the freeze dryer is -80 to -50°C, the freeze drying pressure is 1 to 30 Pa, and freeze drying is performed for 24 to 96 hours; The temperature of the thermal annealing treatment is 300-1600°C, and the time of the thermal annealing treatment is 1-3h; The heating rate to the temperature of the thermal annealing treatment is 1-10℃min -1 ; The reaction is carried out in an inert atmosphere, wherein the inert atmosphere is an argon atmosphere, wherein the argon gas inlet rate is 2 to 40 mL min -1 ; Preferably, the temperature of the thermal annealing treatment is 800-1600° C., and the time of the thermal annealing treatment is 1.5-2.5 h; Preferably, the heating rate to the temperature of the thermal annealing treatment is 4-6°C min -1 ; Preferably, the argon inlet rate is 15-25 mL min -1 .
9. A graphene aerogel for electromagnetic shielding, characterized in that: The graphene aerogel for electromagnetic shielding is obtained by any preparation method described in claims 1-8.
10. The graphene aerogel for electromagnetic shielding according to claim 9, characterized in that: The graphene aerogel has a pore size distribution of 30 to 100 μm, a porosity of at least 95%, and an apparent density of 3 to 15 mg cm -3 , conductivity is 300~1000Sm -1 ;Electromagnetic shielding rate is 20~90dB; thermal conductivity is 20~50mW m -1 K -1 ; Preferably, the graphene aerogel has a resilience of ≥90% under a compression strain of 90%; a plastic deformation of ≤15% after 1000 cycles of 50% compression strain; and a maximum stress reduction of ≤25% after 1000 cycles of 50% compression strain.
Citation Information
Patent Citations
Electromagnetic shielding silicon rubber / graphene / silver nanowire nano composite material and preparation method thereof
CN108165018A
A high-temperature resistant elastic graphene aerogel material and its preparation method
CN112536004B
Preparation method of high-elasticity hydrophobic graphene / nanocellulose composite aerogel
CN114891267A
Preparation method of porous graphene-polymer composite material
CN103408786A
Graphene aerogel microspheres and preparation method thereof
CN106185908A